RISE: Good bacteria that lower cholesterol: myth or truth? / Prof. Dr Kalavathy Ramasamy ... [et al.] - Ramasamy, Kalavathy; Lim, Siong Meng; Sabirin, Faezah; Rohawi, Nur Syakila (Office of the Deputy Vice-Chancellor (Research & Innovation), 2021)
Probiotics, more widely known as the "good" bacteria, are increasingly recognised for their beneficial effects in health maintenance.